BEM modelling of a hydrodynamic lifting surface working in ground proximity - Cosgun, Taner; Ozdemir, Yavuz Hakan (ELSEVIER SCI LTD, 2024)
Present paper aims to assess the performance and limits of boundary element method for the reliable simulation of ground effect phenomena on hydrodynamic lifting surfaces. Benefitting from the ground effect, especially in extreme ground proximity, suggests a promising concept for lifting bodies. On the other hand, the more pronounced the ground effect, the more complicated flow physics it exhibits, making the problem harder to handle numerically. In this study, a potential-based boundary element method (BEM) is applied to the flow past a 3D rectangular wing within a wide range of ground clearances corresponding to out of ground effect (OGE), in ground effect (GE) and extreme ground effect (EGE) conditions. Both positive and negative angles of attack are tested to examine the lift and downforce producing cases. The potential flow around the airfoil is computed using the mixed constant-strength source and constant-strength dipole based panel method. The results show that BEM successfully predicts the lift force variation for a wing working in ground proximity (GE). However, approaching the bounds of extreme ground effect is seen to introduce a progressive decrease of the fidelity of the method. A similar tendency is observed in the downforce generating conditions, which is also an important scenario for ground vehicle aerodynamics. BEM remarkably overestimates the magnitude of the downforce when the ground clearance reaches up to the EGE conditions, still, it produces quite satisfactory results for the rest of the tested configurations. The pressure distributions are also provided to examine the flow field in the aforementioned cases. Overall, the results lead us to conclude that BEM stands as a robust and reliable prediction tool for ground effect on 3D wings but the extreme ground effect condition represents the limit of its accuracy range.
Keywords: Ground effect; Boundary element method; Potential flow; Aerodynamics; 3d wing; Extreme ground effect; Downforce; AERODYNAMIC CHARACTERISTICS; WINGS; STABILITY; Engineering; Mathematics